Study of short term outcome and incidence of recurrence of inguinal hernia rep air in Hospital Universiti Sains malaysia - Wan Zainira, Wan Zain (2008)
The purposes of this study are to evaluate the complications arise from the inguinal hernia repair and their correlations with the patients' factors and surgical procedure's factors. The aim is to improve our service. Surgical Unit in Hospital Sains Malaysia offers the surgery for inguinal hernia repair. This retrospective study was done on 600 patients who undergone the hernia repair. This study started from January 2000 until January 2005. About 580 male patients and 18 female patients had undergone hernia repair within the time frame. Mean age was 52 years old with standard deviation of 18.2 years. We found patients more than 50 years old tend to develop short term complications and overall complications after the surgery (p<0.05). 364 patients have right sided hernia, 200 patients have left sided hernia and 36 have bilateral hernia. 494 patients have indirect hernia, 93 patients have direct hernia, 7 patients have both direct and indirect hernia and 6 patients have sliding hernia Indirect hernia have higher risk to develop recurrent hernia (0<0.05). Majority of patients came to hospital for the treatment after 1 to 6 years of symptoms. 460 had undergone Lichteinstein repair, 121 had undergone Darning repair, 10 had Bassini and 9 had Iaparoscopic hernioplasty. Type of surgery does not alter the incidence of complications and recurrence after the surgery. 537 patients had elective surgery and 63 patients had emergency surgery. Duration of operation was longer in emergency surgery in which the duration of more than 2 hours were 17.7% in elective cases comparing to 49.2% in the emergency cases (p<O.OS) and emergency cases stayed longer in hospital comparing to elective cases (p<O.OS). 87 patients had COAD (chronic obstructive airway disease), 45 had chronic constipation and 39 had BPH ( benign prostatic hypertrophy ). Patients who had COAD tend to come as emergency and develop short term complication after the surgery (p<O.OS). There were 23 wound infections. Our wound infection rate was at 3.8%. The less experienced surgeons had shown to have higher early infection rate comparing to the more experienced surgeons (p<O.OS). There were I9 recurrent cases. 6 patients recurred as early as less than 6 months. 6 recurred after 6 month but less than I year, 7 recurred after I year to 5 years after the surgery. The indirect hernia have higher recurrent rate. Similarly with patients who develop post operative complication, the recurrent rate was higher in this group (p<O.OS) In summary, the commonest complications post hernia repair were wound infection, scrotal hematoma and recurrence. Patients age of more than 50 years old, patients who have COAD and less experienced surgeons had increased the risk of post operative complications. Patients who have indirect hernia and who developed post operative complications have higher risk to develop recurrence.